Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0202632
|View full text |Cite
|
Sign up to set email alerts
|

Depth of invasion (DOI) as a predictor of cervical nodal metastasis and local recurrence in early stage squamous cell carcinoma of oral tongue (ESSCOT)

Abstract: BackgroundThe new AJCC staging system (8th edition) incorporates depth of invasion to stage oral cancers. It is a recognized predictor for neck nodal metastasis and local recurrence, the associated risk is not well defined. The aim of this study was to explore the risk of occult neck nodal metastasis and local recurrence in relation to depth in early stage squamous cell carcinoma of oral tongue.MethodsWe have evaluated records of 179 patients with early tongue cancer treated in our unit from 2006–2015 with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 18 publications
2
70
1
Order By: Relevance
“…Thus, future studies should follow the definition of DOI and the cutoff values predefined by AJCC for OSCC, that is, ≤5 mm, >5 mm and ≤10 mm, >10 mm (AJCC, ; Lydiatt et al, ). From the available studies, the only one adopting these cutoff values (Faisal et al, ) reported odds ratio of 1.69 (≤5 mm vs. >5 mm and ≤10 mm), 2.15 (>5 mm and ≤10 mm vs. >10 mm), and 3.63 (≤5 mm vs. >10 mm) for occult lymph node metastasis. Interestingly, one recent study opens a new avenue toward the usefulness of machine learning algorithms in the prediction of occult lymph node metastasis in early‐stage OSCC (Bur et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, future studies should follow the definition of DOI and the cutoff values predefined by AJCC for OSCC, that is, ≤5 mm, >5 mm and ≤10 mm, >10 mm (AJCC, ; Lydiatt et al, ). From the available studies, the only one adopting these cutoff values (Faisal et al, ) reported odds ratio of 1.69 (≤5 mm vs. >5 mm and ≤10 mm), 2.15 (>5 mm and ≤10 mm vs. >10 mm), and 3.63 (≤5 mm vs. >10 mm) for occult lymph node metastasis. Interestingly, one recent study opens a new avenue toward the usefulness of machine learning algorithms in the prediction of occult lymph node metastasis in early‐stage OSCC (Bur et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As noted many years ago, nodal metastasis has a profound and dismal impact on prognosis, with a 50% reduction of 5-year DSS in patients showing positive neck nodes (1). DSS for tongue SCC decreases, passing from T2 to T3N0 disease, as the prevalence of loco-regional recurrence greatly increases for an infiltration deeper than 10 mm (10, [14][15][16]. According to many studies, in fact, 10 mm is the threshold of DOI predicting a decline in both DSS and disease-free survival (DFS) for tongue cancer (10,(13)(14)(15).…”
Section: Validation?mentioning
confidence: 96%
“…The cut-off commonly used to stratify patients into low and high risk is 4 mm [2]. DOI is an important prognostic factor for nodal metastasis in oral tongue cancer, with increasing DOI associated with nodal involvement and worse prognosis [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated no benefit to adding radiation therapy (RT) for deeper tumors [5][6][7][8][9]. O'steen et al retrospectively evaluated the outcomes of 32 patients with stage N0-2b oral tongue or floor of mouth cancers with the primary tumor not crossing the midline who underwent PORT.…”
Section: Introductionmentioning
confidence: 99%